Pengaruh Differentiated Instruction melalui Model Pembelajaran Berbasis Masalah terhadap Prestasi Belajar Siswa Sekolah Menengah Pertama - Amalia Buntu; Supriyatman; Syech Zainal (Jurnal Penelitian Pendidikan IPA, 2025)
Effective learning must accommodate the unique needs of each learner. The combination of differentiated learning with PBL has not been widely revealed. This study aims to see the effect of differentiated learning through the Problem-Based Learning (PBL) model on student learning achievement. The research method used was a quasi-experiment using control and experimental classes. Data was collected through pretest and post-test. The control class used conventional learning, while the experimental class used differentiated learning with the PBL model. The results showed that using differentiated learning through the PBL model affected student learning achievement, with a sig value of 0.001 on the Mann-Whitney test. The average Normalized Gain (N Gain) of the control class was 0.32, while in the experimental class, it was 0.45. Both are in the medium category. In the control class, the N-Gain scores of individual students in the low, medium, and high categories were 52%, 40%, and 8%, respectively. The experimental class was 12%, 76%, and 12%, respectively. The improvement in student learning achievement in the experimental class is better than in the control class. Differentiated instruction provides access for students to be facilitated with their different needs, while with PBL, students can learn through contextualized problem-solving steps. Overall, it can be concluded that differentiated learning through the PBL model influences student learning achievement.